The Effects of Multi-Level Diversity on Team Innovation: The Role of Collaborative Capability - Adams, Ravi; Pratiwi, Anggun; Sudirman, Wahyu Febri Ramadhan (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2024)
Objective: This study examines the effects of surface-level, deep-level, and functional-level diversity on team innovation. This study also examines the moderation effect of the collaborative capability toward diversity and team innovation. Design/methodology/approach – The sample for this research was 175 creative team members who were then integrated into 38 creative teams of radio and television broadcasting institutions. Data collection was done using a survey method. Findings – This study indicates that surface-level and deep-level diversity negatively impact team innovation, while functional-level diversity has a positive. In addition, the study found that collaborative capability has been moderated on surface-level diversity and team innovation. However, collaborative capability does not moderate the effect of deep- and functional-level diversity on the innovation team. Originality/value – This research contributes to the team innovation literature by examining the influence of three characteristics of team diversity consisting of surface level, deep level, and functional comprehensively on team innovation, as well as the moderating role of collaboration capability as a contextual factor. Practical/Policy implication: From a practical perspective, this study has important implications for how practitioners in creative teams overcome surface and deep-level diversity challenges and take advantage of the functional-level diversity of members in creative teams. This research also increases understanding of the value of diversity in the context of team innovation.